DOKTRIN ULTRA VIRES KEPADA DIREKTUR UTAMA TERHADAP PENYELEWENGAN RANTAI PASOKAN PEMBIAYAAN (STUDI PT. WASKITA KARYA PERSERO TBK): The Ultra Vires Doctrine on The President Director Regarding Supply Chain Financing Conduct (Study PT. Waskita Karya Persero) - Mush’ab Abdul Jabbar; Heru Pringgodani Sanusi (Faculty of Law, Universitas Trisakti, 2025)
The Board of Directors is the main organ responsible for managing the Company, tasked with acting in its best interest according to Article 92 of Law Number 40 of 2007. This discussion focuses on the application of the Ultra Vires Doctrine in the case of supply chain financing misconduct at PT Waskita Karya and the Board’s responsibility under Law Number 19 of 2003 on State-Owned Enterprises and Law Number 40 of 2007 on Limited Liability Companies. The research employs a normative juridical approach, descriptive in nature, using secondary data analyzed qualitatively and concluded deductively. The Ultra Vires Doctrine applies here because the Board’s actions exceeded its authority as outlined in Article 3 of the Company’s Articles of Association and violated Article 5, paragraph (3) of Law Number 19 of 2003. Regarding the Board's responsibility, Article 97, paragraph (2) of Law Number 40 of 2007 holds each director personally liable for company losses caused by negligence or error. Additionally, shareholders can file a civil lawsuit under Article 61 of Law Number 40 of 2007, referencing Article 1365 of the Civil Code, if harmed by the decisions of the General Meeting of Shareholders (GMS), Board of Directors, or Board of Commissioners.